Gender effect on the relationship of time limit at 100% VO2max with other bioenergetic characteristics - Billat, V.; Beillot, J.; Jan, J.; Rochcongar, P.; Carre, F. (Medicine & Science in Sports & Exercise, 1996)
The aim of this study was to investigate the influence of gender on the possible contribution of tlim at Va max (minimal speed that elicits VO2max) in performance speeds. The male and female elite middle-distance runners had similar performance (IAAF scores). Fourteen female and fifteen male (25.2 +/- 3.6 and 25.1 +/- 4.2 yr old; VO2max = 63.2 +/- 4.2 and 77.7 +/- 6.4 ml.kg-1 min-1; Va max = 17.3 +/- 0.7 and 20.8 +/- 1.1 km.h-1, respectively) performed three exercise tests on a treadmill (3 degrees slope) within a 2-wk period: an incremental test to determine VO2max, Va max and the velocity at the onset of blood lactate accumulation (VOBLA); an exhaustive constant velocity test to determine tlim at Va max; and an exhaustive constant velocity test at 110% Va max to determine the accumulated oxygen deficit (AOD). There were no effects of gender, i.e., no significant differences were observed between female and male for tlim at Va max (421 +/- 129 vs 367 +/- 118 s respectively; P = 0.24), VOBLA as % Va max (88.4 +/- 2.7 vs 90.4 3% of Va max; P = 0.07), AOD (40.1 +/- 14.9 vs 48.9 +/- 21.3 ml.O2.kg-1; P = 0.22), running economy at the same absolute speed, i.e., 14 km.h-1 (53.4 +/- 2.6 vs 52.7 +/- 4.1 ml.O2.min-1.kg-1; P = 0.64) nor for gross oxygen cost of running (CR) at the same relative velocity (75% Va max) (0.214 +/- 0.001 vs 0.214 +/- 0.002 ml.O2.kg-1.m-1; P = 0.94). However, an effect of gender was found on the relationship between the bioenergetic parameters and performance. For male, v1500 was predicted by Va max, VOBLA, tlim at 110% of Va max, and CR (R2 = 0.96). For female, no bioenergetic parameters were strongly correlated with v1500 m. The inverse relationship found between Va max and tlim at Va max in previous literature was confirmed by the 29 runners in this study and for the subset of male only.